Transnational attention, domestic agenda-setting and international agreement: modeling necessary and sufficient conditions for media-driven humanitarian interventions - Junk, Julian; Blatter, Joachim (2010)
Abstract: "Interventions based solely or partially on humanitarian grounds are rare; but, over the course of the last two decades, they have become increasingly common phenomena of international politics. Nevertheless international relations theories have thus far not been able to adequately account for their occurrence. The authors present a theoretical framework to explain humanitarian interventions as a result of a multilevel process driven by media attention and political entrepreneurship. They argue that drawing the developed world's public attention to a humanitarian crisis does not suffice to prompt international political reaction to it-it is only a necessary but not a sufficient condition. They therefore develop a consistent, detailed, and falsifiable theoretical model that systematically traces the necessary steps from the spaces of a humanitarian tragedy through the domestic arenas of potentially intervening states to the international arena where agreements on interventions must